Global and Regional Migration Frameworks: A Case Study on the Rohingya Displacement - Zahangir, Moinuddin; Pramanik, Pooja Rani; Hossain, Imran; Emon, Fahim Ahmed (Religion and Policy Journal, 2025)
Research Problem: Forced migration has become one of the most critical humanitarian challenges of the 21st century. The Rohingya refugee crisis highlights fundamental weaknesses in existing global and regional governance systems, particularly in addressing systemic persecution, statelessness, and large-scale displacement. The crisis also exposes the unequal responsibility borne by host countries such as Bangladesh and the inadequacy of international and regional responses. Research Purposes: This study aims to critically examine the structural causes of the Rohingya crisis, assess the effectiveness of international and regional refugee protection frameworks, and identify governance gaps in managing forced migration. It seeks to evaluate how current systems fail both refugees and host states, and to explore lessons for improving global migration governance. Research Methods: The research employs a qualitative policy analysis approach. It is based on a comprehensive review of legal instruments, policy frameworks, and relevant scholarly literature related to refugee protection, forced migration, and international governance mechanisms. Results and Discussion: The analysis reveals persistent systemic persecution and statelessness of the Rohingya people, alongside a disproportionate burden placed on Bangladesh as the primary host country. Major refugee protection frameworks, including the 1951 UN Refugee Convention and the Global Compact on Refugees, are found to lack binding burden-sharing obligations and effective enforcement mechanisms. Regional organizations such as ASEAN and SAARC demonstrate limited capacity and coordination in responding to the crisis, resulting in fragmented and insufficient protection. Research Implications and Contributions: The study underscores the urgent need for a global migration governance framework that is equitable, sustainable, enforceable, and rights-based, while providing fair support to host countries. By using the Rohingya crisis as a case study, this research contributes to broader debates on forced migration and offers policy-relevant insights for reimagining international and regional responses in an increasingly interconnected and crisis-prone world.